2016
DOI: 10.1515/sjph-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children and adolescents with cerebral palsy

Abstract: IntroductionIn a cross-sectional cohort study, health-related quality of life of Slovenian children and adolescents with cerebral palsy was examined, and factors associated with it have been identified.MethodsCaregivers of 122 children and adolescents with cerebral palsy were addressed to fill out proxy versions of HRQoL questionnaires (DISABKIDS generic and cerebral palsy module). Children and adolescents without cognitive deficit were asked to fill out the self-report versions.ResultsNinety-one families of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
3
20
1
1
Order By: Relevance
“…This applies particularly to such elements of the PedsQL questionnaire as the feeling of fear, sadness, anger, or establishing relationships with peers. Although most interventions aim to improve physical independence, a lot more could be done in the wider society to improve social inclusion and participation of children with CP [45].…”
Section: Discussionmentioning
confidence: 99%
“…This applies particularly to such elements of the PedsQL questionnaire as the feeling of fear, sadness, anger, or establishing relationships with peers. Although most interventions aim to improve physical independence, a lot more could be done in the wider society to improve social inclusion and participation of children with CP [45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show the poor quality of life of this population when compared to healthy adolescent (6,(8)(9) , highlighting the need for research on all aspects of quality of life of adolescents with cerebral palsy, especially in low and middle income countries (9)(10)(11) . In addition, the limitation of centers specialized in rehabilitation in the care of adolescents with cerebral palsy is notorious.…”
Section: Introductionmentioning
confidence: 92%
“…The limitations become more evident at a stage in life that imposes countless challenges. Personality disorders and the search for autonomy and independence, inherent to adolescence, face the dependence on their caregivers to perform many activities (3,(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional cohort study which examined the HRQoL in children and adolescents with CP reported the higher rate of HRQoL in children, followed by adolescents and, in the end, parents. An explanation could be the way in which children feels the limitations and restrictions, which have different significance as the child becomes adolescent, while the parents/caregivers tend to compare their children with healthy children [30]. In 2018 Ozkan compared children's QoL and mothers' burden in different types of CP and established that the lowest children's QoL score was reached in quadriplegia, followed by hemiplegia and diplegia, and demonstrated the existence of a significant negative correlation between mothers' burden and child's QoL [31].…”
Section: Introductionmentioning
confidence: 99%